(untitled) (Journal of Philosophy Culture and Political Science, 2021)
The important problem of consciousness has often been declared unsolvable by the methods of traditional empirical sciences. It has been argued that all objects of the empirical sciences can be fully analyzed in structural terms, but that consciousness is (or has) something beyond its structure. However, modern neurobiology has introduced a theoretical framework in which the non-structural aspects of consciousness, namely the so-called qualitative properties that can be analyzed in structural terms, are also evident. This structure allows us to view them as something compositional with internal structures that fully define their qualitative nature. Moreover, it is possible to identify those internal structures that represent certain neural patterns. The totality of all explicit neural representations has a detailed and precise correlation with the content of a person’s consciousness. Since all the essential nodes responsible for explicit neural representations are also associated with brain planning modules, this means that the functional structure of the entire network of explicit neural representations will actually be the functional structure of the corresponding consciousness. Thus, consciousness as a whole can be viewed as a complex neural pattern that misperceives some of its very complex structural properties. Keywords: philosophy of mind, qualia, consciousness, difficult problem, structuralism.